Genomic analysis and molecular profiling of dengue viruses in Sabah, Malaysia, during 2019-2020 - Mya Myat Ngwe Tun; Jecelyn Leaslie John; Takeshi Nabeshima; Abdul Marsudi Manah; Yuki Takamatsu; Takeshi Urano; Kouichi Morita; Kamruddin Ahmed (Elsevier Ltd, 2025)
Objectives: Limited information is available on the distribution of dengue virus (DENV) serotypes and genotypes in Borneo, particularly in Sabah, as most studies have focused on Peninsular Malaysia. This study aimed to investigate the serological and molecular epidemiological characteristics of DENV in patients from Sabah. Methods: Serum samples were collected from febrile patients in Kota Kinabalu and Lahad Datu between 2019 and 2020 at the Kota Kinabalu Public Health Laboratory. We performed virus isolation, serological testing, viremia quantification, and complete genome sequencing. Results: Among 188 serum samples, 89 tested positive for DENV by RT-qPCR: 20 DENV-1, 46 DENV-2, 20 DENV-3, and 1 DENV-4. A total of 38 viruses were successfully isolated. Isolates belonged to DENV-1 (Genotypes I and IV), DENV-2 (Cosmopolitan genotype), and DENV-3 (Genotypes I and III). Phylogenetic analysis revealed close relationships with strains from Malaysia, Indonesia, and the Philippines. DENV-2 was the predominant serotype, while the highest viremia levels were observed in DENV-3-infected patients. Conclusions: This study provides the first detailed phylogenetic and complete genome analysis of DENV in Sabah. Continued molecular surveillance is essential to enhance our understanding of dengue transmission and to support effective control strategies.